2009
DOI: 10.1002/jgm.1386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunogenicity of an anti‐caries vaccine encoding a cell‐surface protein antigen of Streptococcus mutans by intranasal DNA prime‐protein boost immunization

Abstract: The results obtained in the present study suggest that the intranasal DNA prime-protein boost vaccination regimen is a novel strategy for the practical application of DNA vaccine against dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…In particular, microand nano-particle delivery systems that encapsulate protein antigens or DNA that encode for antigens have been evaluated. However, the focus of intranasal vaccination has often been on the treatment of infectious diseases 29,[41][42][43][44][45][46][47] . Nonetheless, a recent study has demonstrated that nanoparticles composed of modified c-polyglutamic acid (c-PGA) encapsulating full length OVA protein instilled intranasally induced anti-tumor immunity against melanoma 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, microand nano-particle delivery systems that encapsulate protein antigens or DNA that encode for antigens have been evaluated. However, the focus of intranasal vaccination has often been on the treatment of infectious diseases 29,[41][42][43][44][45][46][47] . Nonetheless, a recent study has demonstrated that nanoparticles composed of modified c-polyglutamic acid (c-PGA) encapsulating full length OVA protein instilled intranasally induced anti-tumor immunity against melanoma 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, micro- and nano-particle delivery systems that encapsulate protein antigens or DNA that encode for antigens have been evaluated. However, the focus of intranasal vaccination has often been on the treatment of infectious diseases2941424344454647. Nonetheless, a recent study has demonstrated that nanoparticles composed of modified γ-polyglutamic acid (γ-PGA) encapsulating full length OVA protein instilled intranasally induced anti-tumor immunity against melanoma48.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of S-IgA antibodies on the adhesion of S. mutans MT8148 to S-HA beads was examined as previously described [20] . Briefly, 5 mg of HA beads were equilibrated in buffered KCl at room temperature overnight.…”
Section: The Adherence Inhibition Assaymentioning
confidence: 99%